Implementasi Model Pembelajaran Kooperatif Tipe Make A Match Untuk Meningkatkan Kemampuan Problem Solving Matematika Siswa - Sopia, Nurapni Sopia; Jiran Dores, Olenggius; Hadidi, Hadidi; Bahasa Indonesia, Bahasa Indonesia (Jurnal PEKA (Pendidikan Matematika), 2024)
This study was motivated by the low mathematics problem-solving ability of seventh-grade students of SMP Negeri 3 Belimbing Hulu. The purpose of the research was to improve students' math problem-solving skills by using Make-A-Match Cooperative Learning Model. The research used a qualitative descriptive approach with a form of classroom action research consisting of two cycles. The research instruments used were problem-solving ability test questions, observation sheets, questionnaires, and documentation. Based on the results of research and data processing from 22 students, the percentage of students' math problem-solving completeness increased from cycle I to cycle II, namely 59% to 100%, these results show that students are able to achieve the average. The increase in students' math problem-solving ability from cycle I to cycle II obtained an average of 67 to 83, these results indicate that the level of students' math problem-solving ability is in the high category. Furthermore, students' responses to the Make-A-Match Cooperative Learning Model were in the excellent category with an average student score of 80. So it can be concluded that the Make-A-Match Cooperative Learning Model can improve the mathematics problem-solving ability of seventh-grade students.